Exploring the culture of food safety : the role of organizational influencers in motivating employees’ safe food-handling practices. - Ungku Zainal Abidin, Ungku Fatimah; Arendt, Susan W.; Strohbehn, Catherine H. (Routledge, 2013)
The role of organizational influencers on foodservice employees’ motivation to follow safe handling practices was explored. Data were collected from 311 employees with no supervisory responsibilities working in commercial and non-commercial foodservices. Employees identified level of agreement with eight organizational influencers that motivate them to follow safe food-handling practices. Data were analyzed to determine if differences in motivation by influencers existed among employees with different demographic characteristics. Age, years of foodservice experience and work status impacted motivations of both commercial and non-commercial employees. Future research could test a comprehensive measure of organizational influencers on employees’ safe food-handling practices.